Inductive Low‐Frequency Processes in PEMFC‐Impedance Spectra. Issue 4 (5th March 2020) - Schiefer, A.; Heinzmann, M.; Weber, A.
Abstract: Impedance spectra of polymer electrolyte membrane (PEM) fuel cells often comprise an "inductive loop" at low frequencies from 1 Hz to 1 mHz additionally to the typically polarization resistances with capacitive behavior between 1 MHz to 1 Hz. To investigate this inductive behavior, systematic variations of operating parameters as humidity, current density and gas compositions are performed. The impedance spectra, including their inductive parts, are deconvoluted by an extended version of the distribution of relaxation times (DRT). Two inductive processes are identified in the DRT and subsequently quantified by fitting the spectra to an extended equivalent circuit model exhibiting negative resistances and constant phase elements. Both inductive processes are depending on relative humidity and current density. The inductive behavior seems to be dominated by the oxygen reduction reaction (ORR) at the cathode, whereas changes in membrane hydration can be excluded as the main cause for the inductive low‐frequency processes. Measurements in symmetrical H2 /H2 operating mode prove that the inductive behavior cannot be solely related to the ORR. The ratio of the inductive processes to the ohmic and capacitive loss processes ranges from 15% to 30%. Thus, a considerable cell performance improvement related to the existence of these inductive low‐frequency processes has to be taken into account.